Education: Public or Social Service? Immersing the Concept in the Costa Rican Context - Sibaja Núñez, Enrique (2009)
It is convenient to start these lines with some questions. Will being able to supply water to a population have the same implications in the short, medium and long term as being able to provide access to educational services?